“Theoretical, methodological and terminological issues regarding indirect translation: An overview.” - Rosa, Alexandra Assis (2017)
This article offers and overview of the current main theoretical, terminological and methodological issues regarding indirect translation defined as a translation of a translation. The first section on terminological issues addresses the terminological and semantic diversity involved in the metalanguage, clarifies terminological discrepancies and patterns, motivations, and consequences. The second section on conceptual issues highlights an array of main variables used to address indirect translation, and produces a classification based mainly on the number of intervening texts, languages and their choice, though considering further variables for the subcategorization of indirectness. The third section on methodological issues stresses the time-consuming nature of a process encompassing contextual and textual analyses, of texts and paratexts, and lists main features symptomatic of indirectness. After a brief presentation of the special issue, the article ends by identifying several open issues and further research avenues to catalyse further research on indirect translation.